The NEWS-G detector at SNOLAB. (1st February 2023) - Balogh, L.; Beaufort, C.; Brossard, A.; Caron, J.-F.; Chapellier, M.; Coquillat, J.-M.; Corcoran, E.C.; Crawford, S.; Dastgheibi-Fard, A.; Deng, Y.; Dering, K.; Durnford, D.; et al.
Abstract: The New Experiments With Spheres-Gas (NEWS-G) collaboration intends to achieve sub-GeV/c 2 Weakly Interacting Massive Particles (WIMPs) detection using Spherical Proportional Counters (SPCs). SPCs are gaseous detectors relying on ionisation with a single ionization electron energy threshold. The latest generation of SPC for direct dark matter searches has been installed at SNOLAB in Canada in 2021. This article details the different processes involved in the fabrication of the NEWS-G experiment. Also outlined in this paper are the mitigation strategies, measurements of radioactivity of the different components, and estimations of induced background event rates that were used to quantify and address detector backgrounds.